Effect of Rhus coriaria extract on wound healing potential in Sprague Dawley rats - Amin, Zahra Abdulqader (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Rhus coriaria, a well-known spice grown in the Kurdistan region of Iraq, commonly known in the Middle East Region by (Sumac), is reported to enclose many medical benefits. This study assessed the effects of topical application of Rhus coriaria extract on the rate of wound closure, the Hydroxyproline (HXP) and Nitric Oxide (NO) levels were measured using the healed skin tissue homogenate the elemental composition of the plant was screened. Methods: Adult male Sprague Dawley rats were topically treated with 0.2 mL of the vehicle (gum accacia), Intrasite gel (positive control), 100 and 200 mg/kg of Rhus coriaria extract. Results: Wounds dressed with the extract and Intrasite gel healed significantly earlier than those with the vehicle. The high content of HXP and NO proves that the effect of Rhus coriaria extract on an excision wound model was significantly higher than that of the vehicle itself. The highest mineral contents were in Potassium, Calcium, Phosphorus, Magnesium and the extract was rich in energy content. Conclusion: The current study concluded that Rhus coriaria showed high potential in wound healing activity.